Silicon dioxide aerogel powder and preparation method thereof
By mechanically mixing powder a, powder b and foaming powder under a sealed environment, silica aerogel powder is prepared, which solves the problem of poor mechanical properties, and achieves significant improvement in mechanical properties and optimization of application scenarios.
Patent Information
- Application Number
- CN202510200042.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-24
- Publication Date
- 2025-03-25
AI Technical Summary
The existing silica aerogel powder has poor mechanical properties, especially when used as composite materials, which significantly reduces the mechanical properties of the material.
Silica aerogel powder is prepared by mechanically mixing powder a, powder b and foaming powder under a sealed environment. Powder a is made from cellulose nanofiber reinforced silica sol, and powder b is foamed to form a foamed body with holes, and the silica aerogel is located in the holes of the foamed body to provide support.
It significantly improves the mechanical properties of silica aerogel powder, including compressive strength and impact toughness, optimizes its application scenarios, and extends the service life of the material by adding antioxidant ingredients.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aerogels and relates to silicon dioxide aerogel powder and a preparation method thereof. Background Art
[0002] SiO 2 Aerogel is a highly dispersed solid material with nano-scale particles aggregated to form a nanoporous network structure, and the pores are filled with gaseous dispersion medium. Due to its nanoporous structure, low density, low dielectric constant, low thermal conductivity, high porosity, high specific surface area and other characteristics, it shows unique properties in mechanics, acoustics, thermal, optics and other aspects, and has extensive and huge application value in many fields such as aerospace, military, petroleum, chemical industry, minerals, communications, medicine, building materials, electronics, metallurgy, etc. The unique nanoporous structure of aerogel also leads to its extremely poor mechanical properties. When it is used as a component of a composite material, it will significantly reduce the mechanical properties of the material. Summary of the invention
[0003] The object of the present invention is to provide a silica aerogel powder and a preparation method thereof, so as to solve the problem of poor strength of the aerogel powder mentioned in the background technology.
[0004] The purpose of the present invention can be achieved through the following technical solutions: A silicon dioxide aerogel powder, comprising the following raw materials in parts by weight: Powder a 10.6-16.4 parts, powder b 33.7-38.5 parts, foaming powder 6.8-8.5 parts; The silica aerogel powder is prepared by the following steps: In a sealed environment, powder a, powder b and foaming powder are uniformly mixed by mechanical mixing to obtain silica aerogel powder.
[0005] Furthermore, the foaming powder is high-temperature microsphere foaming powder.
[0006] Wherein, powder a is prepared by the following steps: Step A1, after ethyl orthosilicate, ethanol and deionized water are mixed and stirred evenly, 1% by mass hydrochloric acid is added dropwise with stirring, and after the precursor is fully hydrolyzed, 0.1 mol / L ammonia water is added dropwise with stirring to obtain a silica sol; Step A2, adding cellulose nanofibers to the silica sol prepared in step A1, stirring for 20-40 minutes, standing at 30-80° C. for 30-150 minutes, and then mechanically crushing for 5-10 minutes to obtain a composite wet gel; Step A3, the composite wet gel prepared in step A2 is successively treated with ethanol and supercritical CO 2Solvent replacement and supercritical drying are performed to obtain powder a.
[0007] Furthermore, in step A1, the dosage ratio of ethyl orthosilicate, ethanol, deionized water, hydrochloric acid and ammonia water is 31.3-34.2 mL: 35.7-41.2 mL: 11.6-12.5 mL: 0.6-1 mL: 3-4 mL.
[0008] Furthermore, the usage ratio of the silica sol and the cellulose nanofibers in step A2 is 100 mL: 1-5 g.
[0009] Wherein, cellulose nanofibers are prepared by the following steps: Step S1, clean the dead bark, dry it at 55-65°C, grind it into powder, mix the powder with 0.5 mol / L NaOH solution at a ratio of 1:25 (w / v), then heat it to 95-98°C and keep it for 3-4 hours, filter and wash the residue with gauze, and dry it at 62-65°C to obtain a residue; Step S2, mixing the residue with a sodium nitrite acetate buffer solution (0.9% sodium nitrite, 3.2% sodium hydroxide and 9% glacial acetic acid) at a ratio of 1:20 (w / v), reacting at 80-85° C. for 3-4 hours, filtering the sample, washing with ultrapure water until neutral, and freeze-drying to obtain a mixture; Step S3, mixing the mixture with ultrapure water at a ratio of 1:80-90 (w / v), then rapidly dispersing at a rotation speed of 12000-15000 rpm for 1-2 minutes, then ultrasonicating for 40-60 minutes, freeze-drying, and grinding to obtain cellulose nanofibers.
[0010] Wherein powder b is prepared by the following steps: Step C1, add suberic acid, hexamethylenediamine, dodecanediamine and 2 / 3 parts by weight of a free radical initiator into a three-necked flask, mix well, heat to 65-67° C., stir and react for 4-5 hours, continue to heat to 140-145° C., and carry out polycondensation reaction for 0.5-1.5 hours to obtain a prepolymer; Step C2, add paraffin, benzoic acid and prepolymer into a three-necked flask and stir evenly, heat to 240-245°C and react for 1-1.5h, cool to 50-54°C, add the remaining mass part of free radical initiator, then add modified filler, continue stirring for 2-4h, cool, granulate and grind to obtain powder b.
[0011] Furthermore, the weight proportions of the suberic acid, hexamethylenediamine, dodecanediamine, free radical initiator, paraffin, benzoic acid and modified filler are: 33.2-46.4 parts of suberic acid, 64.2-104.5 parts of hexamethylenediamine, 12.8-16.4 parts of dodecanediamine, 0.8-1.1 parts of paraffin, 0.1-0.2 parts of benzoic acid, 3.5-4.1 parts of free radical initiator and 6.7-7.5 parts of modified filler.
[0012] Furthermore, the free radical initiator is azobisisobutyronitrile.
[0013] The modified filler is prepared by the following steps: Step D1, add malonic acid, acetone, iodine and acetic anhydride into a three-necked flask, stir and react at 32-36° C. for 5 h, cool, add water to precipitate, and obtain intermediate 1; The reaction process is as follows: Step D2, add 2-hydroxybenzaldehyde, intermediate 1 and purified water into a three-necked flask, reflux for 11-12 hours, cool and filter, wash with ice water to obtain intermediate 2; The reaction process is as follows: Step D3, add intermediate 2 and thionyl chloride into a three-necked flask, reflux for 12 hours, and evaporate the solvent under reduced pressure to obtain intermediate 3; The reaction process is as follows: Step D4, add camphene and potassium thiocyanate to a three-necked flask, control the reaction temperature to 80-88°C, add 78% concentrated sulfuric acid by mass, react for 6-7h, cool, extract, 0.5mol / L NaHCO 3 The solution was washed with water and recrystallized to obtain intermediate 4; The reaction process is as follows: Step D5, add intermediate 4, hydrazine hydrate with a mass fraction of 82%, and anhydrous ethanol into a three-necked flask, reflux for 60-80 minutes, cool and precipitate, and recrystallize from ethanol to obtain intermediate 5; The reaction process is as follows: Step D6, adding intermediate 3, intermediate 5, potassium carbonate and toluene into a reaction kettle, reacting for 7-10 hours at a rotation speed of 250-350 r / min and a temperature of 65-70° C. to obtain a modified filler.
[0014] The reaction process is as follows:
[0015] Furthermore, the usage ratio of malonic acid, acetone, iodine and acetic anhydride in step D1 is 11.4-12.7 g: 7.4-8.2 g: 0.1-0.15 g: 15-18 mL.
[0016] Furthermore, the usage ratio of 2-hydroxybenzaldehyde, intermediate 1 and purified water in step D2 is 2.3-2.5 g: 3.1-3.5 g: 30-35 mL.
[0017] Furthermore, the usage ratio of the intermediate dichloride and thionyl chloride in step D3 is 3.7-4.1 g: 15-18 mL.
[0018] Furthermore, the usage ratio of camphene, potassium thiocyanate and concentrated sulfuric acid in step D4 is 21.5-22.6 g: 17.6-18.3 g: 15-20 mL.
[0019] Furthermore, the usage ratio of the intermediate tetrakis, hydrazine hydrate and anhydrous ethanol in step D5 is 8.6-10.1 g: 4.3-5.7 g: 150-160 mL.
[0020] Furthermore, in step D6, the molar ratio of intermediate three to intermediate five is 1:1, and the amount of potassium carbonate used is 15-17% of the mass of intermediate five.
[0021] A silicon dioxide aerogel powder, comprising the following preparation method: In a sealed environment, powder a, powder b and foaming powder are uniformly mixed by mechanical mixing to obtain silica aerogel powder.
[0022] Beneficial effects of the present invention: The present invention provides a silica aerogel powder and a preparation method thereof. The aerogel powder is prepared by uniformly mixing powder a, powder b and foaming powder by mechanical mixing in a sealed environment. The problem of poor mechanical properties of single-component silica aerogel is solved. The prepared silica aerogel powder has high quality, excellent mechanical properties, simple preparation method, safe preparation process and extremely low risk factor. Firstly, monodispersed cellulose nanofibers are used as reinforcing agents to strengthen the gel skeleton of silica aerogel powder, so as to solve the problem that the mechanical properties of aerogel powder will be seriously damaged when it is used as a component of a composite material. This method actually changes the internal skeleton structure of aerogel to enhance its mechanical strength. Secondly, powder b is foamed by the foaming powder to form a foamed body with holes. The effective component of powder a, silica aerogel, can be located in the holes of the foamed body, playing an effective role of supporting the aerogel. This method supports the aerogel skeleton by external anchoring force, thereby enhancing its own mechanical strength. The combined effect of the two internal and external forces greatly improves the strength of silica aerogel powder, optimizing its application scenarios. In addition, modified fillers are added to slow down the oxidation aging rate of the material, maintain the mechanical strength of the material, and extend its service life. The components with antioxidant properties are thiosemicarbazone and benzopyrone. Camphene is used as a raw material to synthesize thiosemicarbazone. Camphene compounds themselves have antioxidant activity. At the same time, some derivatives of thiosemicarbazone also have potential antioxidant effects, and have excellent protective effects against oxygen, heat, ozone, light, bending and copper damage; benzopyrone compounds have various activities such as antioxidant, antibacterial, anticancer, and anti-inflammatory. The introduction of benzopyrone can significantly improve the antioxidant capacity of thiosemicarbazone, and at the same time, it causes the diversification of benzopyrone substituents, and also makes it have the ability to quench free radicals, thereby greatly improving the antioxidant properties of the substrate and effectively maintaining the mechanical strength of the material. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Example 1: 11.4g malonic acid, 7.4g acetone, 0.1g iodine, 15mL acetic anhydride were added to a three-necked flask, stirred at 32°C for 5 h, cooled, and precipitated with water to obtain an intermediate 1; 2.3g 2-hydroxybenzaldehyde, 3.1g intermediate 1 and 30mL pure water were added to a three-necked flask, refluxed for 11h, cooled and filtered, and washed with ice water to obtain an intermediate 2; 3.7g intermediate 2 and 15mL thionyl chloride were added to a three-necked flask, refluxed for 12h, and the solvent was evaporated under reduced pressure to obtain an intermediate 3; 21.5g camphene and 17.6g potassium thiocyanate were added to a three-necked flask, the reaction temperature was controlled at 80°C, 15mL of concentrated sulfuric acid with a mass fraction of 78% was added thereto, the reaction was continued for 6h, cooled, extracted, 0.5mol / L NaHCO 3 The solution was washed with water and recrystallized to obtain intermediate four; 8.6 g of intermediate four, 4.3 g of hydrazine hydrate with a mass fraction of 82%, and 150 mL of anhydrous ethanol were added to a three-necked flask, refluxed for 60 min, cooled and precipitated, and recrystallized from ethanol to obtain intermediate five; intermediate three, intermediate five, potassium carbonate, and toluene were added to a reactor, and reacted for 7 h at a speed of 250 r / min and a temperature of 65°C to obtain a modified filler, wherein the molar ratio of intermediate three to intermediate five is 1:1, and the amount of potassium carbonate is 15% of the mass of intermediate five.
[0025] Example 2: 11.9g malonic acid, 7.7g acetone, 0.12g iodine, 17mL acetic anhydride were added to a three-necked flask, stirred at 34°C for 5 h, cooled, and precipitated with water to obtain an intermediate one; 2.4g 2-hydroxybenzaldehyde, 3.3g intermediate one and 33mL pure water were added to a three-necked flask, refluxed for 11h, cooled and filtered, and washed with ice water to obtain an intermediate two; 3.9g intermediate two and 16mL thionyl chloride were added to a three-necked flask, refluxed for 12h, and the solvent was evaporated under reduced pressure to obtain an intermediate three; 22.3g camphene and 17.9g potassium thiocyanate were added to a three-necked flask, the reaction temperature was controlled to 85°C, 17mL of concentrated sulfuric acid with a mass fraction of 78% was added thereto, the reaction was reacted for 6h, cooled, extracted, 0.5mol / L NaHCO 3 The solution was washed with water and recrystallized to obtain intermediate four; 9.5 g of intermediate four, 5.3 g of hydrazine hydrate with a mass fraction of 82%, and 155 mL of anhydrous ethanol were added to a three-necked flask, refluxed for 70 min, cooled and precipitated, and recrystallized from ethanol to obtain intermediate five; intermediate three, intermediate five, potassium carbonate, and toluene were added to a reactor, and reacted for 9 h at a speed of 300 r / min and a temperature of 68°C to obtain a modified filler, wherein the molar ratio of intermediate three to intermediate five is 1:1, and the amount of potassium carbonate is 16% of the mass of intermediate five.
[0026] Example 3: 12.7g malonic acid, 8.2g acetone, 0.15g iodine, 18mL acetic anhydride were added to a three-necked flask, stirred at 36°C for 5 h, cooled, and precipitated with water to obtain an intermediate 1; 2.5g 2-hydroxybenzaldehyde, 3.5g intermediate 1 and 35mL pure water were added to a three-necked flask, refluxed for 12h, cooled and filtered, and washed with ice water to obtain an intermediate 2; 4.1g intermediate 2 and 18mL thionyl chloride were added to a three-necked flask, refluxed for 12 h, and the solvent was evaporated under reduced pressure to obtain an intermediate 3; 2.6g camphene and 18.3g potassium thiocyanate were added to a three-necked flask, the reaction temperature was controlled at 88°C, 20mL of 78% concentrated sulfuric acid was added thereto, the reaction was reacted for 7h, cooled, extracted, 0.5mol / L NaHCO 3 The solution was washed with water and recrystallized to obtain intermediate four; 10.1 g of intermediate four, 5.7 g of hydrazine hydrate with a mass fraction of 82%, and 160 mL of anhydrous ethanol were added to a three-necked flask, refluxed for 80 min, cooled and precipitated, and recrystallized from ethanol to obtain intermediate five; intermediate three, intermediate five, potassium carbonate, and toluene were added to a reactor, and reacted for 10 h at a speed of 350 r / min and a temperature of 70°C to obtain a modified filler, wherein the molar ratio of intermediate three to intermediate five is 1:1, and the amount of potassium carbonate is 17% of the mass of intermediate five.
[0027] Example 4: Clean the dead bark, dry it at 55°C, grind it into powder, mix the powder with 0.5 mol / L NaOH solution at a ratio of 1:25 (w / v), then heat it to 95°C and keep it for 3 hours, filter and wash the residue with gauze, and dry it at 62°C to obtain a residue; mix the residue with sodium nitrite acetate buffer solution (0.9% sodium nitrite, 3.2% sodium hydroxide and 9% glacial acetic acid) at a ratio of 1:20 (w / v), react at 80°C for 3 hours, filter the sample, wash it with ultrapure water until it is neutral, and freeze-dry it to obtain a mixture; mix the mixture with ultrapure water at a ratio of 1:80 (w / v), then quickly disperse it at a speed of 12000 rpm for 1 minute, then ultrasonicate it for 40 minutes, freeze-dry it, and grind it to obtain cellulose nanofibers.
[0028] Example 5: Clean the dead bark, dry it at 60°C, grind it into powder, mix the powder with 0.5 mol / L NaOH solution at a ratio of 1:25 (w / v), then heat it to 96°C and keep it for 3 hours, filter and wash the residue with gauze, and dry it at 63°C to obtain a residue; mix the residue with sodium nitrite acetate buffer solution (0.9% sodium nitrite, 3.2% sodium hydroxide and 9% glacial acetic acid) at a ratio of 1:20 (w / v), react at 82°C for 3 hours, filter the sample, wash it with ultrapure water until it is neutral, and freeze-dry it to obtain a mixture; mix the mixture with ultrapure water at a ratio of 1:85 (w / v), then quickly disperse it at a speed of 12000 rpm for 1 minute, then ultrasonicate it for 45 minutes, freeze-dry it, and grind it to obtain cellulose nanofibers.
[0029] Example 6: Clean the dead bark, dry it at 65°C, grind it into powder, mix the powder with 0.5 mol / L NaOH solution at a ratio of 1:25 (w / v), then heat it to 98°C and keep it for 4 hours, filter and wash the residue with gauze, and dry it at 65°C to obtain a residue; mix the residue with sodium nitrite acetate buffer solution (0.9% sodium nitrite, 3.2% sodium hydroxide and 9% glacial acetic acid) at a ratio of 1:20 (w / v), react at 85°C for 4 hours, filter the sample, wash it with ultrapure water until it is neutral, and freeze-dry it to obtain a mixture; mix the mixture with ultrapure water at a ratio of 1:90 (w / v), and then quickly disperse it at a speed of 15000 rpm for 2 minutes, then ultrasonicate it for 60 minutes, freeze-dry it, and grind it to obtain cellulose nanofibers.
[0030] Example 7: After 31.3 mL of tetraethyl orthosilicate, 35.7 mL of ethanol and 11.6 mL of deionized water were mixed and stirred evenly, 0.6 mL of 1% hydrochloric acid was added dropwise with stirring, and after the precursor was fully hydrolyzed, 3 mL of 0.1 mol / L ammonia water was added dropwise with stirring to obtain a silica sol; 1 g of cellulose nanofibers prepared in Example 4 was added to 100 mL of the silica sol, and the mixture was stirred for 20 min and then allowed to stand at 30 ° C for 30 min, and then mechanically crushed for 5 min to obtain a composite wet gel; the composite wet gel was successively precipitated with ethanol and supercritical CO 2 Solvent replacement and supercritical drying are performed to obtain powder a.
[0031] Example 8: After 33.2 mL of tetraethyl orthosilicate, 37.6 mL of ethanol and 11.8 mL of deionized water were mixed and stirred evenly, 0.7 mL of 1% hydrochloric acid was added dropwise with stirring, and after the precursor was fully hydrolyzed, 3.5 mL of 0.1 mol / L ammonia water was added dropwise with stirring to obtain a silica sol; 3 g of cellulose nanofibers prepared in Example 5 were added to 100 mL of the silica sol, and the mixture was stirred for 30 min and then allowed to stand at 55 ° C for 60 min, and then mechanically crushed for 7 min to obtain a composite wet gel; the composite wet gel was successively precipitated with ethanol and supercritical CO 2 Solvent replacement and supercritical drying are performed to obtain powder a.
[0032] Example 9: After 34.2 mL of tetraethyl orthosilicate, 41.2 mL of ethanol and 12.5 mL of deionized water were mixed and stirred evenly, 1 mL of 1% hydrochloric acid was added dropwise with stirring, and after the precursor was fully hydrolyzed, 4 mL of 0.1 mol / L ammonia water was added dropwise with stirring to obtain a silica sol; 5 g of cellulose nanofibers prepared in Example 6 were added to 100 mL of the silica sol, stirred for 40 min, and then allowed to stand at 80 ° C for 150 min, and then mechanically crushed for 10 min to obtain a composite wet gel; the composite wet gel was successively precipitated with ethanol and supercritical CO 2 Solvent replacement and supercritical drying are performed to obtain powder a.
[0033] Example 10: Add suberic acid, hexamethylenediamine, dodecanediamine and 2 / 3 parts by weight of azobisisobutyronitrile to a three-necked flask, mix well, heat to 65°C, stir and react for 4 hours, continue to heat to 140°C, and polycondense for 0.5 hours to obtain a prepolymer; add paraffin, benzoic acid, and prepolymer to a three-necked flask, stir well, heat to 240°C, react for 1 hour, cool to 50°C, add the remaining parts by weight of azobisisobutyronitrile, Add the modified filler prepared in Example 1, continue stirring for 2 hours, cool, granulate, and grind to obtain powder b, wherein the weight parts of suberic acid, hexamethylenediamine, dodecanediamine, azobisisobutyronitrile, paraffin, benzoic acid, and modified filler are: 33.2 parts of suberic acid, 64.2 parts of hexamethylenediamine, 12.8 parts of dodecanediamine, 0.8 parts of paraffin, 0.1 parts of benzoic acid, 3.5 parts of azobisisobutyronitrile and 6.7 parts of modified filler.
[0034] Example 11: Add suberic acid, hexamethylenediamine, dodecanediamine and 2 / 3 parts by weight of azobisisobutyronitrile to a three-necked flask, mix evenly, heat to 66°C, stir and react for 4 hours, continue to heat to 142°C, and carry out polycondensation reaction for 1 hour to obtain a prepolymer; add paraffin, benzoic acid, and prepolymer to a three-necked flask and stir evenly, heat to 243°C and react for 1 hour, cool to 53°C, add the remaining mass part of azobisisobutyronitrile, and then add the modified filler prepared in Example 2, continue stirring for 3 hours, cool, granulate, and grind to obtain powder b, wherein the weight parts of suberic acid, hexamethylenediamine, dodecanediamine, azobisisobutyronitrile, paraffin, benzoic acid, and modified filler are: 40.6 parts of suberic acid, 87.3 parts of hexamethylenediamine, 14.1 parts of dodecanediamine, 0.9 parts of paraffin, 0.1 parts of benzoic acid, 3.7 parts of azobisisobutyronitrile and 7.2 parts of modified filler.
[0035] Example 12: Add suberic acid, hexamethylenediamine, dodecanediamine and 2 / 3 parts by weight of azobisisobutyronitrile to a three-necked flask, mix well, heat to 67°C, stir and react for 5 hours, continue to heat to 145°C, and react for 1.5 hours to obtain a prepolymer; add paraffin, benzoic acid, and prepolymer to a three-necked flask, stir well, heat to 245°C, react for 1.5 hours, cool to 54°C, and add the remaining parts by weight of azobisisobutyronitrile. , then add the modified filler prepared in Example 3, continue stirring for 4 hours, cool, granulate, and grind to obtain powder b, wherein the weight parts of suberic acid, hexamethylenediamine, dodecanediamine, azobisisobutyronitrile, paraffin, benzoic acid, and modified filler are: 46.4 parts of suberic acid, 104.5 parts of hexamethylenediamine, 16.4 parts of dodecanediamine, 1.1 parts of paraffin, 0.2 parts of benzoic acid, 4.1 parts of azobisisobutyronitrile and 7.5 parts of modified filler.
[0036] Example 13: A silica aerogel powder comprising the following raw materials in parts by weight: 10.6 parts of powder a prepared in Example 7, 33.7 parts of powder b prepared in Example 10, and 6.8 parts of high-temperature microsphere foaming powder; The silica aerogel powder is prepared by the following steps: In a sealed environment, powder a, powder b and high-temperature microsphere foaming powder are uniformly mixed by mechanical mixing to obtain silica aerogel powder.
[0037] Example 14: A silica aerogel powder comprising the following raw materials in parts by weight: 13.7 parts of powder a prepared in Example 8, 34.2 parts of powder b prepared in Example 11, and 7.5 parts of high-temperature microsphere foaming powder; The silica aerogel powder is prepared by the following steps: In a sealed environment, powder a, powder b and high-temperature microsphere foaming powder are uniformly mixed by mechanical mixing to obtain silica aerogel powder.
[0038] Example 15: A silica aerogel powder comprising the following raw materials in parts by weight: 16.4 parts of powder a prepared in Example 9, 38.5 parts of powder b prepared in Example 12, and 8.5 parts of high-temperature microsphere foaming powder; The silica aerogel powder is prepared by the following steps: In a sealed environment, powder a, powder b and high-temperature microsphere foaming powder are uniformly mixed by mechanical mixing to obtain silica aerogel powder.
[0039] Comparative Example 1: Silica aerogel powder produced by Green Building Technology Co., Ltd.
[0040] Comparative Example 2: The preparation method of the silica aerogel powder of Comparative Example 2 refers to Example 13, except that no cellulose nanofibers are added.
[0041] Comparative Example 3: The preparation method of the silica aerogel powder of Comparative Example 3 refers to Example 14, except that no modified filler is added.
[0042] The silica aerogel powders obtained in Examples 13-15 and Comparative Examples 1-3 were subjected to the following performance tests: (1) the porosity was tested by nitrogen isothermal elution method; (2) the hydrophobic angle was tested by the θ / 2 method; (3) the sample was allowed to stand and its compressive strength was measured. The test results are shown in Table 1: Table 1
[0043] It can be seen from Table 1 that, compared with Comparative Examples 1-3, the silica aerogel powders prepared in Examples 13-15 have high compressive strength, high impact toughness, and high mechanical strength, and have broad application prospects.
[0044] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
Claims
1. A silica aerogel powder, characterized in that: The raw materials include the following parts by weight: 10.6-16.4 parts of powder a, 33.7-38.5 parts of powder b, and 6.8-8.5 parts of foaming powder; Wherein powder b is prepared by the following steps: Step C1, add suberic acid, hexamethylenediamine, dodecanediamine and 2 / 3 parts by weight of a free radical initiator into a three-necked flask, mix well, heat to 65-67° C., stir and react for 4-5 hours, continue to heat to 140-145° C., and carry out polycondensation reaction for 0.5-1.5 hours to obtain a prepolymer; Step C2, add paraffin, benzoic acid and prepolymer into a three-necked flask and stir evenly, heat to 240-245°C and react for 1-1.5h, cool to 50-54°C, add the remaining mass part of free radical initiator, then add modified filler, continue stirring for 2-4h, cool, granulate and grind to obtain powder b.
2. The silica aerogel powder according to claim 1, characterized in that: Powder a is prepared by the following steps: Step A1, after ethyl orthosilicate, ethanol and deionized water are mixed and stirred evenly, hydrochloric acid is added dropwise with stirring, and then ammonia water is added dropwise with stirring to obtain a silica sol; Step A2, adding cellulose nanofibers to the silica sol prepared in step A1, stirring evenly, standing at 30-80° C., and then mechanically crushing to obtain a composite wet gel; Step A3, the composite wet gel obtained in step A2 is subjected to solvent replacement with ethanol and supercritical CO2 in sequence, and then supercritically dried to obtain powder a.
3. The silica aerogel powder according to claim 1, characterized in that: The modified filler is prepared by the following steps: Step D1, add malonic acid, acetone, iodine and acetic anhydride into a three-necked flask, stir and react at 32-36° C. for 5 h, cool, add water to precipitate, and obtain intermediate 1; Step D2, add 2-hydroxybenzaldehyde, intermediate 1 and purified water into a three-necked flask, reflux for 11-12 hours, let stand to cool, filter, and wash with ice water to obtain intermediate 2; Step D3, add intermediate 2 and thionyl chloride into a three-necked flask, reflux for 12 hours, and evaporate the solvent under reduced pressure to obtain intermediate 3; Step D4, adding camphene and potassium thiocyanate into a three-necked flask, controlling the reaction temperature to 80-88° C., adding concentrated sulfuric acid thereto, reacting, cooling, extracting, washing with water, and recrystallizing to obtain intermediate four; Step D5, add intermediate 4, hydrazine hydrate and anhydrous ethanol into a three-necked flask, reflux for 60-80 min, cool and precipitate, and recrystallize from ethanol to obtain intermediate 5; Step D6, adding intermediate 3, intermediate 5, potassium carbonate and toluene into a reaction kettle to react and obtain a modified filler.
4. The silica aerogel powder according to claim 2, characterized in that: Cellulose nanofibers are prepared by the following steps: Step S1, clean and dry the dead bark, grind it into powder, mix the powder with NaOH solution, and then heat it to 95-98°C and keep it for 3-4 hours, filter and wash the residue with gauze, and dry it to obtain a residue; Step S2, mixing the residue and sodium nitrite acetate buffer solution evenly, reacting at 80-85° C. for 3-4 hours, filtering the sample, washing with ultrapure water until neutral, and freeze-drying to obtain a mixture; Step S3, mixing the mixture with ultrapure water, then rapidly dispersing, ultrasonicating, and freeze-drying. Grind to obtain cellulose nanofibers.
5. The silica aerogel powder according to claim 1, characterized in that: The method comprises the following preparation steps: in a sealed environment, powder a, powder b and foaming powder are uniformly mixed by mechanical mixing to obtain silica aerogel powder.